PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Aang Fariz Anwar; Yani Suryani; Adam Malik (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
͞So far, many people think that achieving academic success is a challenge. High intelligence requires high intellectual intelligence (IQ). other factors that influence One of them is emotional intelligence. Emotional intelligence is a person's ability to recognize his own emotions, control them, be motivated, recognize the feelings of others and train the ability to relate to others. While learning outcomes are learning achievements from a learning activity that is carried out based on measurement and assessment of the results of learning activities in the academic field which are manifested in the form of numbers in report cards. The method used in this research is quantitative with a total sample of 32 students from class VII A SMP IT Annibras. The purpose of this study was to determine the extent to which emotional intelligence influences student learning outcomes in PAI subjects, which will later become a reference for schools in efforts to improve student learning outcomes. The Emotional Intelligence of class VII students at SMP IT Annibras is in a very high classification with a percentage of 92.1% as well as student learning outcomes in Islamic Religious Education subjects which are also very high with a percentage of 86.8%. The correlation is 70.6% with the hypothesis that there is a relationship between Emotional Intelligence and student PAI learning outcomes in the strong correlation classification, the effect is also 50% with the statement that Emotional Intelligence influences student PAI Learning Outcomes, in the sense that student PAI learning outcomes are influenced 50% by intelligence emotional and 50% beyond emotional intelligence